ANALYSIS FEASIBILITY OF USING PHOTOVOLTAIC CELLS DEPENDING ON CLIMATIC CONDITIONS PLACEMENT AND CONSUMER POWER - Antypov, E. (Енергетика і автоматика, 2016)
The possibility of the use of energy-efficient systems, energy consumers using solar energy. Calculate the required number of photovoltaic cells, depending on the climatic conditions and the electric power consumers.